2016
DOI: 10.1242/bio.019463
|View full text |Cite
|
Sign up to set email alerts
|

Alternative exon usage creates novel transcript variants of tumor suppressor SHREW-1 gene with differential tissue expression profile

Abstract: Shrew-1, also called AJAP1, is a transmembrane protein associated with E-cadherin-mediated adherence junctions and a putative tumor suppressor. Apart from its interaction with β-catenin and involvement in E-cadherin internalization, little structure or function information exists. Here we explored shrew-1 expression during postnatal differentiation of mammary gland as a model system. Immunohistological analyses with antibodies against either the extracellular or the cytoplasmic domains of shrew-1 consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 42 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…However, there is increasing evidence that the expression of AJAP1 is not restricted to the adherens junction, but depends on the developmental stage and tissue type (Klemmt et al, 2016). To assess the molecular function of AJAP1 underlying angiogenic sprouting, we investigated the cellular localization of endogenous AJAP1 in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, there is increasing evidence that the expression of AJAP1 is not restricted to the adherens junction, but depends on the developmental stage and tissue type (Klemmt et al, 2016). To assess the molecular function of AJAP1 underlying angiogenic sprouting, we investigated the cellular localization of endogenous AJAP1 in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it had been shown that AJAP1 localizes at the plasma membrane in the adhesion complex of epithelial cells, where it binds to the E-cadherin-catenin complex ( Bharti et al, 2004 ). However, there is increasing evidence that the expression of AJAP1 is not restricted to the adherens junction, but depends on the developmental stage and tissue type ( Klemmt et al, 2016 ). To assess the molecular function of AJAP1 underlying angiogenic sprouting, we investigated the cellular localization of endogenous AJAP1 in endothelial cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations